2023
DOI: 10.1021/acs.jmedchem.3c01035
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structure–Activity Relationships, Radiofluorination, and Biological Evaluation of [18F]RM365, a Novel Radioligand for Imaging the Human Cannabinoid Receptor Type 2 (CB2R) in the Brain with PET

Rodrigo Teodoro,
Daniel Gündel,
Winnie Deuther-Conrad
et al.

Abstract: The development of cannabinoid receptor type 2 (CB2R) PET radioligands has been intensively explored due to the pronounced CB2R upregulation under various pathological conditions. Herein, we report on the synthesis of a series of CB2R affine fluorinated indole-2-carboxamide ligands. Compound RM365 was selected for PET radiotracer development due to its high CB2R affinity (K i = 2.1 nM) and selectivity over CB1R (factor > 300). Preliminary in vitro evaluation of [18F]­RM365 indicated species differences in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…PET scans of a rat model with local hCB2R overexpression demonstrated that [ 18 F]5 was able to selectively and reversibly image cerebral CB2R. 6 Dominguez et al report [ 18 F]6 (Figure 1) targeting mutant Huntingtin (mHTT) aggregates in Huntington's disease. In vitro studies showed that 6 has higher mHTT specificity and human metabolic stability than the leading clinical ligand CHDI-180.…”
Section: ■ Radiopharmaceuticals For Brain Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…PET scans of a rat model with local hCB2R overexpression demonstrated that [ 18 F]5 was able to selectively and reversibly image cerebral CB2R. 6 Dominguez et al report [ 18 F]6 (Figure 1) targeting mutant Huntingtin (mHTT) aggregates in Huntington's disease. In vitro studies showed that 6 has higher mHTT specificity and human metabolic stability than the leading clinical ligand CHDI-180.…”
Section: ■ Radiopharmaceuticals For Brain Imagingmentioning
confidence: 99%
“…Moldovan et al report [ 18 F] 5 (Figure ) with high affinity toward human CB2R (hCB2R) and no or low affinity for rat CB2R. PET scans of a rat model with local hCB2R overexpression demonstrated that [ 18 F] 5 was able to selectively and reversibly image cerebral CB2R …”
Section: Radiopharmaceuticals For Brain Imagingmentioning
confidence: 99%